Pengembangan Teknik Steganografi Dengan Kriptografi Modifikasi dari Caesar Cipher dan SHA-256 Untuk Merahasiakan Pesan - Yesi Puspita Dewi (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2020)
Communication using digital media becomes fast and simple. Because of the privacy issue it needs confidential, so security becomes an important. Steganography can hide secret messages into multimedia such as digital image. However, risk factors for steganographic safety is not maximum yet. Steganography techniques are became popular so there are many applications available to uncover secret messages from a stego image, so that the secret messages can be revealed by wrong people. This research improves security on steganography with Caesar Cipher cryptography which has been modified, the secret message then shifted 5 characters and SHA-256, the secret message is then inserted into a digital image with the Least Significant Bit (LSB) method. The tests conducted using qualitative methods with Power Signal Noise Ratio (PSNR) and changes in file size and quantitative methods. From the evaluation with kualitatif method results it is known that file with *.PNG extension have the best result, while kuantitatif method has result 100% success.